Effect of bispidine containing monoterpenoid moieties on physical performance in mice - Kotlyarova, Anastasiya A.; Ponomarev, Konstantin Yu; Morozova, Ekaterina A.; Korchagina, Dina V.; Suslov, Evgeniy V.; Pavlova, Alla V.; Tolstikova, Tatyana G.; Volcho, Konstantin P.; Salakhutdinov, Nariman F. (2020 Cognitive Sciences, Genomics and Bioinformatics (CSGB), 2020)
Increasing physical performance is an urgent task for pharmacology and practical medicine since a decrease in physical performance is a common symptom of many acute and chronic diseases. The aim of this work is to study the effect of monoterpenoid derivatives with 3,7-diazabicyclo [3.3.1] nonane (bispidine) on the physical performance of mice. Physical endurance was studied in two tests: Porsolt forced swimming test with a load of 7% of body weight and running on a treadmill. To assess the effect of the investigated agents on locomotor activity, an open field test was performed. As a result, it was found that, of the two compounds with the codes K1-456 and K1-458, the most effective increase in running and swimming duration is compound K1-458, containing residues of (-) - myrtenal linked to the bispidine moiety through the amino group, at a dose of 100 mg/kg after a single intragastric administration. It was also found that the studied agents statistically significantly increase locomotor activity, distance traveled, speed and reduce the time of the stationary moment when testing in the "open field". Thus, derivatives of bispidine containing monoterpenoid residues are a promising new class of organic compounds for the search for new drugs to increase health.